Extraction of visual information from simplified raster images - R. Badlishah, Ahmad; Syed Alwee Aljunid, Syed Junid; Nebras, N. Hasson (Universiti Malaysia Perlis (UniMAP), 2010)
Simplification of raster images, with irrelevant details of a visual query, eliminates most useless elements, while retaining perceptually dominant elements and shape, speeds up queries. The simplification is widely used for document analysis and recognition as a preprocessing step for high-level object recognition, such as optical character recognition (OCR) andgraphic objects recognition.